Analysis of EFL Teaching in Pakistan: Method and Strategies in the Postmethod Era - Khan, Muhammad Asif Ali (REiLA : Journal of Research and Innovation in Language, 2020)
This study investigates the teaching methods and strategies practised in Pakistan to teach English as a foreign language in the Post-method Era. English language pedagogy in Pakistan has taken a new turn since the establishment of higher education commission and applied linguistic departments in many universities in Pakistan. It focuses on classroom teaching analysis to see what teaching methods and strategies that English language educators in private and public institutes apply. The study applied qualitative methods with five English teachers as Foreign Language (EFL) of the public and private sectors' intermediate level. The participating teachers were given nine open-ended survey questions about the nature of language, language teaching methods, classroom strategies and techniques, and their roles as teachers in the classroom. Findings revealed that EFL teachers in both public and private sectors employ multiple teaching methods and techniques in their classroom practice, rather than holding to one particular method. The data also differentiates teaching methods and strategies of the teachers in the both sectors. Interestingly, it appears that EFL teachers in the private sectors seem to aim at communicative teaching approaches. In contrast, teachers in the public sectors are more inclined to use Grammar Translation Methods (GTM).